2020
DOI: 10.3389/fimmu.2020.572136
|View full text |Cite|
|
Sign up to set email alerts
|

Immunomodulatory Effects of Diterpenes and Their Derivatives Through NLRP3 Inflammasome Pathway: A Review

Abstract: Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein (NLRP) inflammasomes are involved in the molecular pathogenesis of many diseases and disorders. Among NLRPs, the NLRP3 (in humans encoded by the NLRP3 gene) is expressed predominantly in macrophages as a component of the inflammasome and is associated with many diseases, including gout, type 2 diabetes, multiple sclerosis, atherosclerosis, and neurological diseases and disorders. Diterpenes containing repeated isopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 92 publications
(148 reference statements)
1
18
0
Order By: Relevance
“…NLRP3 inflammasome (an innate immune signal complex) is mainly expressed as an inflammasome component in macrophages and is closely related to many diseases, including T2DM, AS, rheumatoid arthritis, gout and neurological diseases ( 64 , 65 ). Various signals, including microbial molecules and abnormal accumulation of cholesterol crystals, can trigger NLRP3 assembly and activation, thereby promoting the conversion and secretion of proIL-1β and proIL-18 into mature forms ( 66 ).…”
Section: Metformin In Regulating Macrophage Dysfunctionmentioning
confidence: 99%
“…NLRP3 inflammasome (an innate immune signal complex) is mainly expressed as an inflammasome component in macrophages and is closely related to many diseases, including T2DM, AS, rheumatoid arthritis, gout and neurological diseases ( 64 , 65 ). Various signals, including microbial molecules and abnormal accumulation of cholesterol crystals, can trigger NLRP3 assembly and activation, thereby promoting the conversion and secretion of proIL-1β and proIL-18 into mature forms ( 66 ).…”
Section: Metformin In Regulating Macrophage Dysfunctionmentioning
confidence: 99%
“…Nuclear factor-kappa B (NF- κ B) is a widely studied transcription factor that is involved in many physiological processes, such as regulating multiple aspects of innate and adaptive immune function [ 17 , 18 ], and as a key mediator of the inflammatory response in regulating inflammatory pain [ 19 ], neuropathic pain [ 20 ], and other chronic pain [ 21 ]. Recent studies have shown that NF- κ B participates in the inflammatory cascade by activating the Nod-like receptor protein 3 (NLRP3) inflammasome in the nucleus [ 22 , 23 ]. The activation of inflammasomes contributes to the development of chronic pain [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide-binding domain leucine-rich repeat (NLR) and pyrin domain containing receptor 3 (NLRP3) comprise the NLRP3 inflammasomes together with apoptosis associated speck like protein and pro-caspase-1 (18,19). Physiological levels of NLRP3 activation protects the body's inflammatory immune system via activation of Caspase-1, whereas uncontrolled activation will lead to dysregulated inflammation, autoimmune diseases, neurodegenerative diseases, and even malignant tumors (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%